Intravenous Magnesium Sulphate for Analgesia after Caesarean Section: A Systematic Review - McKeown, Andrew (Anesthesiol Res Pract, 2017)
OBJECTIVE: To summarise the evidence for use of intravenous magnesium for analgesic effect in caesarean section patients. BACKGROUND: Postcaesarean pain requires effective analgesia. Magnesium, an N-methyl-D-aspartate receptor antagonist and calcium-channel blocker, has previously been investigated for its analgesic properties. METHODS: A systematic search was conducted of PubMed, Scopus, MEDLINE, Cochrane Library, and Google Scholar databases for randomised-control trials comparing intravenous magnesium to placebo with analgesic outcomes in caesarean patients. RESULTS: Ten trials met inclusion criteria. Seven were qualitatively compared after exclusion of three for unclear bias risk. Four trials were conducted with general anaesthesia, while three utilised neuraxial anaesthesia. Five of seven trials resulted in decreased analgesic requirement postoperatively and four of seven resulted in lower serial visual analogue scale scores. CONCLUSIONS: Adjunct analgesic agents are utilised to improve analgesic outcomes and minimise opioid side effects. Preoperative intravenous magnesium may decrease total postcaesarean rescue analgesia consumption with few side effects; however, small sample size and heterogeneity of methodology in included trials restricts the ability to draw strong conclusions. Therefore, given the apparent safety and efficacy of magnesium, its role as an adjunct analgesic in caesarean section patients should be further investigated with the most current anaesthetic techniques.